Broadwater, George Mason - Forgotten Founder - Swedberg, Sarah (Teaching History: A Journal of Methods, 2007)
In this biography, Jeff Broadwater makes the argument for adding Virginian George Mason to the pantheon of founders. Broadwater adds his voice to a recent trend of restoring men whom some scholars believe have been left behind in the history of the American Revolution and early republic, men such as John Jay, Charles Pinckney, and John Witherspoon. While these scholars have not necessarily argued Mason, Jay, Pinckney, or Witherspoon rose to the level of Washington or Jefferson, they want to make sure we get it right, that government policymakers in this important period get their due.